Quantitative analysis of leaching of different metals in human saliva from dental casting alloys: An in vivo study - Ramashanker Siddharth; Roopali Gautam; Pooran Chand; Kaushal Kishor Agrawal; Raghuwar Dayal Singh; Balendra Pratap Singh (Wolters Kluwer Medknow Publications, 2015)
Background: The issue of biomaterial-derived ionic release in various sites of the human body has attracted the interest of many investigators because of the possibility that debris or degradation products elicit a foreign body reaction or have a role in the induction of pathological processes. Purpose: The purpose was to evaluate the saliva of denture wearers after insertion of the prosthesis for leaching of metals from metallic denture. Materials and Methods: Total 20 subjects of age group of 40-60 years including both males (10) and females (10) were selected for the study. Total subjects were divided into 2 groups each containing 10 subjects, Group I (control group): Subjects having dentition intact up to second molar and free of any dental restoration; Group II (study group): Partially edentulous subjects rehabilitated with cast-metal removable partial denture. Saliva samples were taken at three stages that is, 1 h, 24 h and 72 h after the denture insertion from subjects of study group as well as from the control group. Atomic absorption spectroscopy (AAS) was used to estimate the concentration of elemental ions. Obtained data's were analyzed using SPSS (Statistical Package for Social Sciences) version 15.0 statistical analysis software. The values were represented in a number (%) and mean ± standard deviation. Results: At 1 h, 24 h and 72 h after the denture insertion in study group, chromium (Cr) had statistically significant higher mean concentration as compared to manganese (Mn) (P < 0.001). Cr had maximum concentration (0.1479 + 0.0052) immediately after denture insertion while maximum concentration of Mn (0.1479 + 0.0052) was found 24 h after denture insertion. Conclusion: Metal-based dentures show maximum leaching immediately after wearing of the prosthesis which decreased significantly over the period of 3 days. Cr and Mn were the metal ions mainly found in saliva of cast partial denture wearer. No concentration of cobalt, molybdenum (Mo) and iron (Fe) was found in saliva of metal base denture wearer. There was a significant change in concentration of elutes in saliva in first 72 h/3 days making time an effective variable was observed.